Stones from Heaven and Celestial Tricks: The Battle at Gibeon in Joshua 10 - Leonard-Fleckman, Mahri (2017)
Joshua 10 reveals narrative dissonance between two stories: the great Gibeon battle (vv. 10-14) and the story of five kings at the cave at Makkedah (vv. 16-27). I propose that the Gibeon battle preserves an independent, freestanding tradition, upon which the story of the five kings at the cave of Makkedah builds and which eventually expands into a broader vision of conquest in the Book of Joshua. The goal is to understand the logic behind the combination of such distinct narratives in the description of a southern conquest.
Keywords: Makkedah; Gibeon; Literary History; conquest narratives; Joshua 10